Analisis Kebijakan Pemerintah Indonesia dalam Pengajuan dan Penerapan Traffic Separation Scheme (TSS) di Selat Sunda dan Selat Lombok - Muhammad Royyan Fadli; Ismah Rustam; Ahmad Mubarak Munir (The Department of International Relations Universitas Mataram, 2021)
This paper will discuss the motives behind the proposed and implementation of the Traffic Separation Scheme (TSS) in the Sunda and Lombok Strait during the first period of Joko Widodo's reign. During the first period of Joko Widodo's administration, Indonesia submitted a proposal for implementing TSS to the International Maritime Organization (IMO) in 2017. This policy is one of several policies of the Indonesian government in the actualization of the vision of the Global Maritime Nexus (GMN). The two straits, both the Sunda Strait and the Lombok Strait, are considered to have the potential to develop into a busier world shipping route due to their advantages and geostrategic values. In addition to improving shipping safety, applying and applying for a TSS cannot be separated from the aspects of legitimacy, identity and international norms as the motive, based on constructivism. This research uses the following data collection technique: interview, documentation and library study that compiles both primary and secondary data. This research also uses Miles & Huberman’s three stages of data analysis namely, data reduction, data display and drawing conclusions. This research concludes that identities and norms can influence state policies, in this case the submission and implementation of TSS in the Sunda and Lombok Strait.